Demographic analysis towards the understanding of Education Takaful (Islamic Insurance) Plan - Rubayah Yakob,; Hafizuddin-Syah B.A.M,; Nurfarhana Hani Badrul Hisham, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to identify the demographic characteristics affecting the level of understanding of education takaful plan. The data was collected through questionnaires from 145 respondents in Klang Valley, Malaysia, which chosen based on the convenience sampling technique. Results from the independent sample t-test and one-way ANOVA showed that female possess higher level of understanding of education takaful than male. Moreover, workers in the government sector have better understanding on education takaful as compared to self-employed and students. However, there are no significant differences on the understanding of education takaful between government and private sector. This study also found that those who have 1 to 3 children demonstrate higher understanding of education takaful. Overall, the employment sector and number of children had a significant influence on the understanding of education takaful. This study provides a preliminary overview of the demographic factors affecting the understanding of education takaful in Malaysia, which can be used by the takaful industry to strengthen and manage their product development and marketing strategies. It subsequently helps to achieve the target population penetration rate of 25% takaful ownership by 2020.